Systems of Psychotherapy / A Transtheoritical Analysis - Prochaska James O (Brooks/Cole Publishing Company, 1984)
An Integrative Eclectic Framework for Comparing Systems of Psychotherapy, Psychoanalysis, Existential Analysis, Client-Centered Therapy, Gestalt Therapy, Adlerian Therapy, Rational-Emotive Therapy, Transactional Analysis, Emotional Flooding Therapies, Behavior Therapy, Systems Therapies, Comparative Conclusions: Toward a Transtheoretical Therapy, References, Author and Subject Index.